2004
DOI: 10.1177/0887403403255064
|View full text |Cite
|
Sign up to set email alerts
|

Triple Stigma: Persons with Mental Illness and Substance Abuse Problems in the Criminal Justice System

Abstract: This article offers a review of the literature that exists on individuals with dual diagnosis and discusses policies creating the trajectories for mentally ill individuals with substance abuse problems and their community reentry after involvement with the criminal justice system. For this analysis, basic comparisons are made across mentally ill individuals involved with the criminal justice system and the dually diagnosed portion of the population and an analysis of the current trajectory and post-incarcerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
141
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(149 citation statements)
references
References 31 publications
5
141
0
3
Order By: Relevance
“…In one recent study, over three-quarters of inmates with a severe mental disorder also had a cooccurring substance-related disorder; these inmates were more likely to be homeless and to be charged with violent crimes than were other inmates (McNiel, Binder, & Robinson, 2005). A recent review of research that compared offenders with only a mental illness and those with CODs found that those with multiple disorders were more likely to be serving sentences related to their substance use, to be homeless, to violate probation after release, and to recidivate to correctional custody (Hartwell, 2004). Similarly, in a study of over 8,500 offenders in prisonbased therapeutic community substance abuse treatment in California, individuals with CODs were more likely to be under the influence when arrested.…”
Section: Introductionmentioning
confidence: 99%
“…In one recent study, over three-quarters of inmates with a severe mental disorder also had a cooccurring substance-related disorder; these inmates were more likely to be homeless and to be charged with violent crimes than were other inmates (McNiel, Binder, & Robinson, 2005). A recent review of research that compared offenders with only a mental illness and those with CODs found that those with multiple disorders were more likely to be serving sentences related to their substance use, to be homeless, to violate probation after release, and to recidivate to correctional custody (Hartwell, 2004). Similarly, in a study of over 8,500 offenders in prisonbased therapeutic community substance abuse treatment in California, individuals with CODs were more likely to be under the influence when arrested.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this population may require support regarding employment and housing as well as interventions that target mental health problems, problematic substance use, and criminal behavior. The need to develop strategies for treatment, support, and crime prevention particularly targeting these individuals has been repeatedly highlighted [14][15][16].…”
Section: Treatment Utilization and Criminal Recidivism Among Offendermentioning
confidence: 99%
“…Substance abuse is common among offenders with mental health problems [3,14]. Offenders with mental health problems and problematic substance use 1 have multiple treatment needs [14,15].…”
Section: Treatment Utilization and Criminal Recidivism Among Offendermentioning
confidence: 99%
See 1 more Smart Citation
“…According to Fitzpatrick and Myrstol (2011), "the problems of heavy drinking, illicit drug use, and mental illness are also heavily concentrated among those housed in lOCal jails and prisons" (p. 276). The rate of substance abuse and mental illness for inmates ranges between 10% and 90% (Golder et al, 2006;Hartwell, 2004;Kubiak et aI., 2011). Golder et ai.…”
Section: Co-occurring Disordersmentioning
confidence: 99%